Metoda zdyskontowanych dywidend w wycenie przedsiębiorstw - Zarzecki, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The dividend-discount method is based upon the premise that the only cash flow received by stockholders is dividends. While the model is often criticised as being of limited value, it has proven to be surprisingly adaptable and useful in a wide range of circumstances. It may be a conservative model that finds fewer and fewer undervalued firms as market prices rise relative to fundamentals (profits, dividends, etc.), but that can also be viewed as a strength. Tests of the model also seem to indicate its usefulness in gauging value. The model has not been applied in valuing Polish enterprises for privatisation purposes but in a new purely market environment ought to become much more popular. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 549-563